Service of Transportation And Logistics at TPKS Semarang to Shorten The Dwelling Time in AEC Era - Sarjiyanto Sarjiyanto (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2017)
The purpose of this research is to describe the process of dwelling time itself, to identify related parties in the case, and the preparation strategies of Semarang Container Port (TPKS) facing the AEC. The research method used is descriptive, using qualitative and quantitative data. Data collection techniques are interviews with relevant parties, observations, and literature study. The results concluded the process of handling containers in Semarang TPKS potentially huge and causing dwelling time laid in pre-clearance process, customs clearance, and post-clearance process. Parties related to the dwelling time in Semarang Container Port (TPKS) are Custom (DJBC), Importers, and freight forwarding (PPJK). Preparation of Semarang Container Port in facing AEC in order to change the dwelling time by changing a manual system to an online system for clearance process, adding facilities, and improving human resources. The research findings indicate dwelling time length in Semarang Container Port (TPKS) reached 5.6 days which is still far from the government's target of 4.7 days Semarang Container Port (TPKS) has to simplify the system of the pre-clearance process, customs clearance, and post clearance. It needs to be done in order to reduce the length of dwelling time. Optimizations of performance also need to be improved with the Standard Operating Procedure. They also have to immediately perform optimization The Integrated Physical Checking Clearance which operates for 24 hours in one week.